Traditional wireless Communication and its Model in South Asian Region - Dharmakeerthi, Sri Ranjan, G. D. (Marsland Press 310 West 18th Street, New York, NY 10011, USA., 2010)
Traditional wireless Communication is encompassed by the new communication technologies and the heterogeneous vision of a culturally diverse society. This speedy diffusion of latest applications of the new media is exploited for the information and entertainments in the rural locales. As a consequence of this the traditional media net work is being affected at an alarming rate in the periphery. The folk cultural tradition has become to tune pop songs and pop songs associated cultural traditions. These associations mainly occur at the economically and socially marginalized people. These modern information identities, based on the science and technology, are experiencing the western cultural denominations. But the traditional wireless communicational patterns were interconnected collectively with the nature oriented human factors. The newly contextualized model (DSR Model*) on the traditional media based on the Ethnographic approach, discuses the traditional wireless communication system, established in the indigenous territory. [Journal of American Science 2010:6(3) 102-108]. (ISSN: 1545-1003).
Traditional Wireless Communication and its Model in South Asian Region
Keywords: Traditional media, Traditional social context, New Model for the traditional media